Isolation and Antimicrobial Susceptibility Profile of Salmonella and Klebsiella Species from Small Ruminants in University of Maiduguri, Nigeria - Yusuf Madaki Lekko; Enenche Francis Ejeh; Juliana James Ndahi; Fatima Adamu Lawan; Muhammad Mubarak Abba-Kura; Adama Musa Abdullahi (Journal of Applied Veterinary Science And Technology, 2026)
Background: Among the commonly isolated pathogenic bacteria in sheep and goats, Salmonella and Klebsiella species are frequently identified as significant health risks to small ruminants. Purpose:  Critical insights are provided herein to improve the diagnosis, treatment, and management of infections caused by Salmonella and Klebsiella species, thereby enhancing the overall health and productivity of small ruminant populations. Method: Collection was performed on a total of 110 rectal, preputial, and vaginal swab samples from sheep (33) and goats (77). Sub-culturing of the isolates was conducted using Xylose Lysine Deoxycholate (XLD) and Klebsiella selective agar. Subsequent identification was achieved through biochemical assays and an online bacteriological identification system, followed by antimicrobial susceptibility testing in accordance with Clinical and Laboratory Standards Institute (CLSI) guidelines. Data analysis was executed using the Chi-square test, with a p-value of less than 0.05 considered statistically significant. Results: A higher prevalence of Salmonella enterica was observed in sheep (6.1%) compared to goats (2.6%), whereas Klebsiella sp. were found to be more common in goats (19.5%) than in sheep (12.1%). Within the age distribution, the highest prevalence of both Salmonella enterica (6.5%) and Klebsiella sp. (9.7%) was recorded in animals less than one year old. Regarding sex, a higher prevalence of Salmonella enterica was demonstrated in females (4.6%) compared to males (2.2%). High levels of antimicrobial resistance were identified for Cefotaxime 19 (95.0%), CPX-Ciprofloxacin 12 (60.0%), PEF-Pefloxacin 16 (80.0%), AU-Amoxicillin/Clavulanic acid 18 (90.0%), CEP-Cephalexin 16 (80.0%), TRX-Trimethoprim/Sulfamethoxazole 14 (70.0%), and CEF-Ceftriaxone 19 (95.0%). Conversely, the lowest resistance rate was exhibited by OFX-Ofloxacin 3 (15.0%). Conclusion: Ofloxacin is identified as the most effective antimicrobial agent, while cefepime is characterized as the least effective.